Accurate imputation of human leukocyte antigens with CookHLA - Seungho Cook (Nature Portfolio, 2021)
Human leukocyte antigen (HLA) genes influence many immune phenotypes, however methods to impute HLA type have been limited in accuracy. Here, the authors present an HLA imputation method, CookHLA, which uses locally embedded prediction markers to adaptively impute HLA genes across a range of scenarios.